Development and research of counterflow jet mixers of liquid components in agricultural production - Samoichuk, Kyryl; Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Viunyk, Olha; В'юник, Ольга Володимирівна; Вьюник, Ольга Владимировна (My University, 2019)
The process of mixing of the liquid components is quite widespread in agricultural production, for example, in the preparation of uterine (working) solutions of pesticides for spraying gardens, seed dressing, fertilizer solutions for plant nutrition, preparation of animal drug solutions, etc. Among the many designs of mixers for liquid components, the most common devices with mixers.
Keywords: counterflow jet mixers; dispersants; hydraulic devices